(untitled) (Linguostylistic Studies, 2016)
This article deals with the peculiarities of topopoetonyms in the novel «Jacob’s Century» by Volodymyr Lys. The emphasis is laid on the structure and functions of topopoetonyms, their quantitative parameters and dominants, which are considered as the key features and the key aspects of the novel. The semantic characteristics and the role of several types of topopoetonyms in this work of art have been described. In this paper topopoetonym is intepreted as a polyfunctional unit which combines general linguistic functions and peculiar stylistic features. The author states that a topopoetonym in this novel differs from other units and describes some of their distinctive features. Functional features of every individual proper name of the novel have been analyzed. Much attention is also paid to Volodymyr Lys’ individual style presented in the onomastic space of the novel «Jacob’s Century». Key words: the space of proper names, proper name, the sphere of proper names, topopoetonym, functional and semantic peculiarities. References